Energy-aware medium access control protocols for wireless sensors network applications - Barroca, Norberto José Gil (2015)
The main purpose of this thesis was to investigate energy efficient Medium Access Control (MAC) protocols designed to extend the lifetime of a wireless sensor network application, such as tracking, environment monitoring, home security, patient monitoring, e.g., foetal monitoring in the last weeks of pregnancy. From the perspective of communication protocols, energy efficiency is one of the most important issues, and can be addressed at each layer of the protocol stack; however, our research only focuses on the medium access control (MAC) layer. An energy efficient MAC protocol was designed based on modifications and optimisations for a synchronized power saving Sensor MAC (SMAC) protocol, which has three important components: periodic listen and sleep, collision and overhearing avoidance and message passing. The Sensor Block Acknowledgement (SBACK) MAC protocol is proposed, which combines contention-based, scheduling-based and block acknowledgement-based schemes to achieve energy efficiency. In SBACK, the use of ACK control packets is reduced since it will not have an ACK packet for every DATA packet sent; instead, one special packet called Block ACK Response will be used at the end of the transmission of all data packets. This packet informs the sender of how many packets were received by the receiver, reducing the number of ACK control packets we intended to reduce the power consumption for the nodes. Hence more useful data packets can be transmitted. A comparison study between SBACK and SMAC protocol is also performed. Considering 0% of packet losses, SBACK decreases the energy consumption when directly compared with S-MAC, we will have always a decrease of energy consumption. Three different transceivers will be used and considering a packet loss of 10% we will have a decrease of energy consumption between 10% and 0.1% depending on the transceiver. When there are no retransmissions of packets, SBACK only achieve worst performance when the number of fragments is less than 12, after that the decrease of average delay increases with the increase of the fragments sent. When 10% of the packets need retransmission only for the TR1000 transceiver worst results occurs in terms of energy waste, all other transceivers (CC2420 and AT86RF230) achieve better results. In terms of delay if we need to retransmit more than 10 packets the SBACK protocol always achieves better performance when comparing with the other MAC protocols that uses ACK.